Metastasis 2022
DOI: 10.36255/exon-publications.metastasis.dna-damage-response
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response and Cancer Metastasis: Clinical Implications and Therapeutic Opportunities

Ming Yin,
Feng Hong,
Qi-En Wang

Abstract: The DNA damage response (DDR) system is critical to maintain genomic integrity and guard against DNA damages. DDR alterations, resulting from DDR gene mutations or epigenetic modifications, have been involved in cancer initiation, progression, and treatment response.However, the role of DDR alterations in cancer metastasis has not been well characterized.Recently, there is increasing evidence of an important role of DDR in regulating multiple facets of Note to the Reader: This chapter is part of the book Metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Finally, epigenetic alterations of molecular pathways resulting from progression or treatment of primary cancers could potentially pave the ways for other simultaneous malignancies to emerge. For example, DNA damage repair (DDR) alterations, resulting from DDR gene mutations or epigenetic modifications, have been involved in cancer initiation, progression, and treatment response [15]. It has been revealed that DDR genes alterations including BRCA2, BRCA1, CDK12, ATM, FANCD2, or RAD51C affect almost 20% of 333 primary prostate cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, epigenetic alterations of molecular pathways resulting from progression or treatment of primary cancers could potentially pave the ways for other simultaneous malignancies to emerge. For example, DNA damage repair (DDR) alterations, resulting from DDR gene mutations or epigenetic modifications, have been involved in cancer initiation, progression, and treatment response [15]. It has been revealed that DDR genes alterations including BRCA2, BRCA1, CDK12, ATM, FANCD2, or RAD51C affect almost 20% of 333 primary prostate cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the integrity of the genome is crucial for any organism's survival [1]. Double-strand breaks (DSBs) are deemed as one of the most harmful forms of DNA damage since, if left unrepaired, they can result in cell death, or chromosomal rearrangements if inappropriately repaired, leading to cancer [2].…”
Section: Introductionmentioning
confidence: 99%